2018
DOI: 10.18203/2319-2003.ijbcp20181178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamins/tonics prescribing pattern in tertiary care teaching hospital and private sector

Abstract: Background: Rational use of drugs had been great concern by the government as well as public during the past several years. Monitoring of prescriptions studies could identify the associated problems and provide feedback to the prescribers, so as to create awareness about the irrational use of drugs. This study was conducted to evaluate the prescribing pattern of Vitamins/Tonics in government sector and private sector.Methods: This prospective study was designed to obtain statistical data on the prescribing pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…10 In our study, average 1.95 micronutrients were prescribed per patient, which was higher as compared to 0.45 in a study done in Uttar Pradesh (Bhardwaj et al). 11 In our study multivitamin B complex was most commonly prescribed micronutrient followed by vitamin C, folic acid, calcium, zinc, vitamin D3, iron, vitamin A, vitamin B3 and methylcobalamine. Though micronutrients are essential for the skin health, it is overprescribed and this will also cause cost burden on patients.…”
Section: Limitationsmentioning
confidence: 55%
“…10 In our study, average 1.95 micronutrients were prescribed per patient, which was higher as compared to 0.45 in a study done in Uttar Pradesh (Bhardwaj et al). 11 In our study multivitamin B complex was most commonly prescribed micronutrient followed by vitamin C, folic acid, calcium, zinc, vitamin D3, iron, vitamin A, vitamin B3 and methylcobalamine. Though micronutrients are essential for the skin health, it is overprescribed and this will also cause cost burden on patients.…”
Section: Limitationsmentioning
confidence: 55%
“…However, some of the studies conducted in different parts of India have reported much higher percentage of prescriptions containing multivitamins, such as Bhardwaj et al and Hussain et al reported 35.76%-48.57% and 23.12% of the prescriptions containing vitamins and supplements, respectively. 19,20 These supplements need to be prescribed with caution and only in cases where they are indicated because there is every possibility that their use can lead to certain adverse effects as the same has been reported by number of studies including the one study carried out in the United States on dietary supplements. 21 One of the important prescribing parameters is the percentage of the drugs chosen from the EDL of a particular country and WHO requires that every drug should be prescribed from the EDL.…”
Section: Discussionmentioning
confidence: 98%
“…[ 22 23 ] Most of them are prescribed as a part of nutrient supplements in multiple disease conditions such as stroke, diabetes mellitus, and pregnant women and also used as preemptive therapy. [ 24 25 26 ] Most of the preparations are FDCs with numerous active constituents. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] However, some researchers have also revealed the improvement in the quality of life of individuals on multivitamins. [ 22 30 ] The studies conducted in different parts of India like Bhardwaj et al [ 25 ] in Haryana reported 35.76%–48.57% and Hussain et al [ 31 ] in Uttar Pradesh had shown 23.12% of the prescriptions with vitamins and supplements.…”
Section: Discussionmentioning
confidence: 99%